2013
DOI: 10.1002/oby.20137
|View full text |Cite
|
Sign up to set email alerts
|

Permanent activation of HMGA2 in lipomas mimics its temporal physiological activation linked to the gain of adipose tissue

Abstract: Objective: In this study the activation of HMGA2 and overexpression by FGF1-driven stimulation of adipose tissue derived stem cells (ADSCs) in adipose tissue tumors were analyzed. In addition, the expression of HMGA2 and PPAR-gamma mRNA were quantified in canine subcutaneous abdominal adipose tissue from normal and overweight purebred dogs. Design and Methods: ADSCs and adipose tissue explants stimulated with FGF1 followed by gene expression analyses of HMGA2 and p14Arf using Western-blot and qRT-PCR. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…In contrast, constitutional knockout of HMGA2 is associated with a hypoplasia of WAT and a lack of an obese phenotype despite leptin deficiency (Zhou et al 1995). Accordingly, we have proposed that the temporarily strictly scheduled activation of HMGA2 distinguishes the processes in normal adult tissue from the monoclonal gain of adipose tissue underlying the development of lipomas (Thies et al 2013). However, all these results point to a pivotal role of HMGA2 in the gain of adipocytes from their precursors and stem cells, respectively.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast, constitutional knockout of HMGA2 is associated with a hypoplasia of WAT and a lack of an obese phenotype despite leptin deficiency (Zhou et al 1995). Accordingly, we have proposed that the temporarily strictly scheduled activation of HMGA2 distinguishes the processes in normal adult tissue from the monoclonal gain of adipose tissue underlying the development of lipomas (Thies et al 2013). However, all these results point to a pivotal role of HMGA2 in the gain of adipocytes from their precursors and stem cells, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Among the genes that have been linked to a gain of WAT and to T2D by large association studies (Ohshige et al 2011;Voight et al 2010;Zeggini et al 2007) is HMGA2 which has been linked to the development and differentiation of WAT as well. Recently, we had been able to identify an association between the expression of HMGA2 and canine obesity (Thies et al 2013). Based on these finding, we have hypothesized that the temporal activation of HMGA2 in adipose tissue stem cells is a prerequisite not only of normal turnover of adipose tissue but also of its diet-induced hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that high mobility group (HMG) proteins act as architectural factors and coordinate cell proliferation and differentiation in adult adipose tissue [36,37,46]. Research revealed that the HMGA2 gene is frequently disrupted in human solid tumours of a differentiated mesenchymal origin such as lipoma [46].…”
Section: Discussionmentioning
confidence: 99%
“…Totally, 36 articles were identified. Of those, 30 were included in the review: there were 12 case reports [1,9,10,11,26,27,28,29,30,31,32,33,34], 12 reports on basic science or animal studies [4,12,13,35,36,37,38,39,40,41,42,43,44], 2 case series [14,45] and 4 systematic reviews [13,38,46,47]. Totally, more than 60 patients were analysed; 25 articles were studied as a full-text version.…”
Section: Methodsmentioning
confidence: 99%